Molecular dynamics study of ternary system K + K⁺q + O⁻²q - Shimkevich, A.L.; Shimkevich, I.Yu.; Kuzin, V.V. (Condensed Matter Physics, 1999)
Results of molecular dynamics (MD) simulation of potassium/oxygen melt,
K + K⁺q + O⁻²q , at the temperature of 550 K are presented. MD simulation has been performed for oxygen charge −2q = −1, −2 in the frame
of NVT ensemble with only a part of potassium atoms being charged.
Evolution of thermodynamic characteristics of the system has been examined up to t = 9.7 × 10⁻¹⁰ s . Voronoi-Delauney theory of division of space
into polyhedra has been employed to analyze resulting atomic conﬁgurations. Structural and dynamic changes observed, point to the possibility for
oxygen to form clusters in alkali metals. Подані результати моделювання методом молекулярної динаміки
(МД) розплаву калій/кисень K + K⁺q + O⁻²q при температурі 550 K.
МД моделювання виконувались у NVT ансамблі для заряду кисню
−2q = −1, −2 , причому лише частина атомів калію була зарядженою.
Еволюція термодинамічних характеристик системи аналізувалась з
точністю до t = 9.7 × 10⁻¹⁰ s. Для аналізу отримання атомних конфігурацій застосовувалась теорія поділу простору на многогранники Вороного–Делоні. Виявлені структурні та динамічні зміни вказують на можливість формування кисневих кластерів у лужних металах.